Avaliação do sistema de farmacovigilância do Instituto de Doenças Tropicais Natan Portella em Teresina - PI - Amaral, Fabrício Pires de Moura (2006)
Pharmacovigilance is an important weapon for public health, because it allows the prevention of side effects caused by medication. In Brazil, the National Health Surveillance Agency (Anvisa) has priorized the development of activities of post-marketing surveillance in Sentinel Hospitals. The Nathan Portella Institute of Tropical Diseases, located in Teresina-PI was one of the hospitals chosen by the ANVISA to experience the implantation and consolidation of this service. The implantation process was concluded in September, 2005. This effort assessed the pharmacovigilance system introduced in the period between October, 2005 and May, 2006. For such, a check – list applied, 51 anonymous questionnaires to health care workers, and in addition the data on the records and MAE notifications forms were surveyed. The findings were evaluated by using the SPSS software and then compared in order to find failure on information transposed from the records to the notification forms. The check-list applied found organizational failures in the service of hospital pharmacy (absence of SOPs and personnel training records). The questionnaires show that the service was broadcast in wider range among resident doctors and nurses than among the specialist physicians. Also, the survey of data on the records indicated a number of 31 MAE notifications, with 48, 39% (15/31) of reports from doctors against 41,94% (13/31) from nurses. However, by analyzing the forms, it was found that only 16 MAE notifications were filled out – classified under 43,75% (7/16) from nurses against 37,50% (6/16) from resident doctors and 6,25% (1/16) from specialist physicians. It is conclude that there are organizational problems in the pharmacy service aggravated by undernotifications reported by health care workers due to insufficient transposition of data from the records to the spontaneous notification forms.